Empowering Women for Climate Smart Crop-Dairy Farming Systems: Post Harvest Management, Value Chains and Market - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Appropriate technological solutions together with empowering social environment are the basic requirements for ensuring food and livelihood security under the emerging scenario of growing climate risks. Studies by various scientists (Farnworth et. al., 2017; Das et. al., 2015; Chayal et. al., 2013; Waris and Viraktamath, 2013; Dev, 2012; Gosh, 2010) also identified the importance of gender empowerment in agriculture and have found the gender gap in agriculture in India. Through capacity building programs, CIMMYT-CCAFS is aiming to foster Climate Smart Agriculture (CSA) and related activities to women farmers so that issue of knowledge gap between men and women involved in farming is addressed. Similarly a recent workshop was organized to further enhance the role of women in decision making.